PHYSICOCHEMICAL CHANGES IN ROBUSTA COFFEE BEANS DURING HONEY PROCESSING STAGES WITH VARYING FERMENTATION DURATION - Harijono; Talbiyya, Annisa Izzah; Sunarharum, Wenny Bekti (Jurnal Teknologi Pertanian, 2025)
Robusta coffee (Coffea canephora) dominates coffee production in Indonesia. High caffeine content results in a bitter and less varied taste of robusta coffee, leading to its being economically inferior. To increase the value and quality of coffee, post-harvest processing can be modified, such as through honey processing, which involves fermentation. This study evaluated the physicochemical and microbial changes during fermentation, also comparing the honey-processed robusta green beans obtained from 24 and 48 hours of fermentation duration. Observations were conducted at each stage of the process, from pulping until the green bean coffee was obtained. Research parameters during fermentation included chemical tests (moisture, Aw, pH, total sugars, total phenolics) and total microbes count. Color testing (CIE lab) and additional chemical analysis, including total caffeine, were performed on the green coffee beans. Statistical tests were carried out using ANOVA (p<0.05) and Fisher’s test. The findings reveal that fermentation duration affects the microbial population, leads to changes in Aw, and results in a decrease in caffeine content in the resulting green beans.